Negotiating the Voices of ‘Otherness’ in South Africa and the USA: the Function of Humor in Trevor Noah’s Stand-up Comedy on Race - Zách, Lili (AMERICANA E-journal of American Studies in Hungary, 2023)
Comparing Trevor Noah’s stand-up comedy performed in front of South African and US audiences, this paper explores the significance of humor when addressing race relations in the USA and with regard to the system of institutionalized racial segregation known as Apartheid in pre-1994 South Africa. It traces the applicability of John Morreall’s model (2009) to Trevor Noah’s stand-up comedy in relation to the critical, cohesive, and coping functions of humor, originally applied within the context of the Holocaust. While Källstig & Death (2020) discussed the recurring themes of race, disease, and poverty in Noah’s comedy from a postcolonial perspective, this paper proposes to theorize his stand-up comedy by addressing the significance of (American and South African) audiences in the comedian’s assessment of “Otherness” and racial relations. It was Amy Carell (1993) who highlighted the fact that humor did not exist in a vacuum; her Audience-Based Theory of Verbal Humor will be used as the theoretical framework of this paper. Ultimately, by blurring the contrast between tragedy and comedy, the paper applies Morreall’s “positive ethics of humor” and investigates the functions of humor in response to racism in both South Africa and the USA while at the same time assessing the role of audiences to Noah’s performances. In order to emphasize the interconnectedness of humor, psychology, history and politics, the paper traces the uses of laughter in the process of coping with traumatic events that have been associated with politicized racial segregation, hatred, and socio-economic discrimination.